2019
DOI: 10.1002/qj.3510
|View full text |Cite
|
Sign up to set email alerts
|

A two‐fluid single‐column model of the dry, shear‐free, convective boundary layer

Abstract: A single‐column model of the dry, shear‐free, convective boundary layer is presented in which non‐local transports by coherent structures such as thermals are represented by the partitioning of the fluid into two components, updraught and environment, each with a full set of prognostic dynamical equations. Local eddy diffusive transport and entrainment and detrainment are represented by parametrizations similar to those used in eddy diffusivity mass flux schemes. The inclusion of vertical diffusion of the vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(74 citation statements)
references
References 45 publications
(149 reference statements)
5
69
0
Order By: Relevance
“…The assumption that wijT=0 does not imply anything about bijT. In the absence of knowledge of the subfilter‐scale variability, the buoyancy transferred follows Thuburn et al (2019) bijT=θbbi+false(1θbfalse)bj. …”
Section: The Multifluid Boussinesq Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption that wijT=0 does not imply anything about bijT. In the absence of knowledge of the subfilter‐scale variability, the buoyancy transferred follows Thuburn et al (2019) bijT=θbbi+false(1θbfalse)bj. …”
Section: The Multifluid Boussinesq Equationsmentioning
confidence: 99%
“…Thuburn et al (2019) and Weller and McIntyre (2019) presented solutions of two‐fluid equations using the same pressure for both fluids. Thuburn et al (2019) showed that these equations are in fact unstable and can be stabilized by diffusion of vertical velocity whereas Weller and McIntyre (2019) stabilized the equations with diffusion and drag between fluids. Neither of these stabilization techniques are acceptable; sufficient diffusion to stabilize the multifluid equations may smooth out real features of the flow, and the diffusion between fluids and drag used by Weller and McIntyre (2019) meant that both fluids tended to move together rather than through each other.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Holm and Kupershmidt (1984) regularized these equations using multiple pressures for problems with surface tension. Thuburn et al (2019) are also working on a single-column solution of conditionally averaged equations and show that the incompressible conditionally averaged equations are unstable without additional coupling between the fluids.…”
Section: Introductionmentioning
confidence: 99%
“…This behaviour is probably related to the entrainment-detrainment processes and the continuous exchange of particles between fluid 2 and fluid 1. Furthermore, Lagrangian particle tracking is known to produce excessive switching of particle labels between the coherent structures and their environment (see Yeo and Romps 2013;Thuburn et al 2019).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Others (e.g., Angevine 2005) calculate the profile of σ via a vertical integral of the updraft mass budget. More recently, EDMF-like schemes have been introduced in which updraft properties including w, θ , and the area fraction are prognostic variables (Tan et al 2018;Thuburn et al 2019). For all of these schemes, information on the profile of σ and other updraft properties from high-resolution reference simulations is essential either as direct input to the scheme or for calibration and validation.…”
Section: Introductionmentioning
confidence: 99%